The Role of Cadres in the Activeness of Toddler Mothers Coming to the Toddler Posyandu in the Kabila Bone Health Center Work Area - Rensiwati Ampulembang; Raden Maria Veronika Widiatrilupi; Anik Purwati (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Toddler Posyandu has an important role in monitoring child growth and development as well as preventing nutritional and health problems. The activeness of mothers in bringing their toddlers to Posyandu is greatly influenced by various factors, one of which is the role of health cadres. Posyandu cadres act as community mobilizers in increasing awareness and participation of mothers in toddler health programs. However, there are still many mothers who are less active in attending Posyandu, so an evaluation of the influence of the role of cadres on the activeness of toddler mothers in Posyandu activities is needed. Objective: This study aims to determine the relationship between the role of cadres and the activeness of toddler mothers in attending Posyandu toddlers in the work area of Kabila Bone Health Center. Method: This study used a quantitative method with a cross-sectional design. The research sample consisted of 30 respondents selected using a purposive sampling technique. Data collection was carried out through a questionnaire that assessed the role of cadres and the level of mother's activeness in attending Posyandu. Data analysis was carried out using the chi-square test with a significance level of 5% (p <0.05). Results: The results of the study showed that there was a significant relationship between the role of cadres and the activeness of mothers of toddlers in attending the integrated health post, with a p value = 0.000 (<0.05). This shows that the more active and involved the integrated health post cadres are, the higher the level of activeness of mothers in bringing their toddlers to the integrated health post. Conclusion: The role of cadres greatly influences the activeness of mothers in attending the integrated health post for toddlers.